Diversity and distribution of assemblages of estuarine decapod larvae (Crustacea: Decapoda: Anomura, Brachyura) in tropical southeastern Brazil - Magris, R. A.; Fernandes, L. F. Loureiro (Zootaxa, 2011)
Decapod larvae assemblages were studied in the tropical estuaries off southeastern Brazil (Piraquê-açú and Piraquê-mirim rivers estuaries). A total of 32 taxa of decapod larvae were recorded. Brachyuran larvae dominated in Piraquê-açú estuary, with 62% of the relative abundance, and 49% in Piraquê-mirim estuary. Mean larvae concentrations ranged from 17.2 m -3 at Piraquê-mirim (August 2003) to 221.1 m -3 at Piraquê-açú (April 2003). The assemblage of larvae in both estuaries was diverse, especially at Piraquê-mirim, which showed higher ecological stability. The high spatial heterogeneity of the Piraquê-açú and Piraquê-mirim estuarine system resulted in the division of the assemblage into two well-defined groups (truly estuarine and euryhaline). Salinity spatial gradient was a key factor in the structure and distribution of larvae.